Схемное решение построения матричного регистра - Kutsenko, G. V. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
A circuit solution is proposed for constructing an economical matrix register that combines a serial code reception register and a time counter. It can be recommended for implementation as a microchip. It is shown how the use of nontraditional circuit solutions, taking into account new technologies, makes it possible to obtain new qualitative characteristics.